2004
DOI: 10.1111/j.0022-2720.2004.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of receptor arrays in frozen‐hydrated sections and plunge‐frozen specimens of E. coli engineered to overproduce the chemotaxis receptor Tsr

Abstract: SummaryWe have recently reported electron tomographic studies of sections obtained from chemically fixed E. coli cells overproducing the 60-kDa chemotaxis receptor Tsr. Membrane extracts from these cells prepared in the presence of Tween-80 display hexagonally close-packed microcrystalline assemblies of Tsr, with a repeating unit large enough to accommodate six Tsr molecules arranged as trimers of receptor dimers. Here, we report the direct visualization of the Tsr receptor clusters in (i) vitrified cell suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 32 publications
7
75
0
Order By: Relevance
“…First, the head group regions show almost identical mass densities in cryosections, which denotes that the average composition and distribution of head groups do not differ significantly with respect to their masses in either membrane leaflet. By contrast, the asymmetry of the outer membrane of Gram-negative bacteria is clearly visible in cryosections (21,29). This result conflicts with the assumption that the inner leaflet of the mycobacterial outer membrane consists exclusively of mycolic acids with identical carbohydrate head groups and that the outer leaflet is a mixture of extractable lipids containing carbohydrates, peptides, and phosphorylated compounds.…”
Section: Discussionmentioning
confidence: 63%
“…First, the head group regions show almost identical mass densities in cryosections, which denotes that the average composition and distribution of head groups do not differ significantly with respect to their masses in either membrane leaflet. By contrast, the asymmetry of the outer membrane of Gram-negative bacteria is clearly visible in cryosections (21,29). This result conflicts with the assumption that the inner leaflet of the mycobacterial outer membrane consists exclusively of mycolic acids with identical carbohydrate head groups and that the outer leaflet is a mixture of extractable lipids containing carbohydrates, peptides, and phosphorylated compounds.…”
Section: Discussionmentioning
confidence: 63%
“…We have found that immersion of a hippocampal organotypic brain slice in ACSF supplemented with 5% sucrose and 20% dextran for 5 min before freezing is the minimum requirement to achieve reproducible vitrification. Note that 20% dextran is routinely used for extracellular cryoprotection of cell suspension because it produces minimal osmotic effect (17)(18)(19).…”
Section: Establishment Of the Best Freezing Conditionsmentioning
confidence: 99%
“…Structures are preserved down to atomic resolution, and the observed contrast is directly related to density variations in the sample. The method, however, only works for particles or cells that can be squeezed in a sub-micrometer-thick vitreous film.Cryo-electron microscopy of vitreous section (CEMOVIS) was developed to extend the advantage of vitrification to any cell and tissue (7,(16)(17)(18)(19)(20)(21). In general, high-pressure cooling is used to vitrify samples of several hundred-micrometer thickness with minimal addition of cryoprotectant (22).…”
mentioning
confidence: 99%
“…It was further proposed that, in E. coli, trimers of receptor dimers form a hexagonal array with a lattice spacing of 20 nm (13). A subsequent electron cryotomography (ECT) study showed that overexpressed Tsr chemoreceptors in E. coli pack into a hexagonal lattice with a center-to-center spacing of 7.5 nm (14)(15)(16)(17). In these overexpression strains, the receptors surprisingly form a ''zipper-like'' double layer, in which large invaginations of the inner membrane allow the cytoplasmic tips of one layer to interact with the cytoplasmic tips of a second, facing layer.…”
mentioning
confidence: 99%